2014
DOI: 10.1016/j.mspro.2014.07.131
|View full text |Cite
|
Sign up to set email alerts
|

Mossbauer Spectroscopic Study of High Magnetostrictive Cobalt Chromium Ferrites for Automobile Torque Sensors

Abstract: Co-Cr ferrites with the chemical formulae, CoFe 2-x Cr x O 4 (x = 0 to 0.5 in steps of 0.1) were prepared by sol gel autocombustion method. Lattice constants were determined from X-ray diffraction patterns. Magnetic properties were studied by VSM and Mössbauer spectroscopy. Magnetostrictive coefficients were measured using strain gauge technique. The magnetostriction coefficient has been observed to increase sharply at higher chromium concentrations (x = 0.3 -0.5). The hyperfine field H hf values at B-and A-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The magnetostrictive properties depends upon the processing parameters such as synthesis method, pressure applied while making pellets, sintering atmosphere, temperature and sintering time. 4,[52][53][54][55][56][57][58][59] It is reported that the higher magnetostriction and strain derivatives can be obtained when compacted under high pressure ($150 MPa). [52][53][54][55][56][57][58][59] From Fig.…”
Section: Magnetostrictive Properties (L and Dl/dh)mentioning
confidence: 99%
See 3 more Smart Citations
“…The magnetostrictive properties depends upon the processing parameters such as synthesis method, pressure applied while making pellets, sintering atmosphere, temperature and sintering time. 4,[52][53][54][55][56][57][58][59] It is reported that the higher magnetostriction and strain derivatives can be obtained when compacted under high pressure ($150 MPa). [52][53][54][55][56][57][58][59] From Fig.…”
Section: Magnetostrictive Properties (L and Dl/dh)mentioning
confidence: 99%
“…4,[52][53][54][55][56][57][58][59] It is reported that the higher magnetostriction and strain derivatives can be obtained when compacted under high pressure ($150 MPa). [52][53][54][55][56][57][58][59] From Fig. 6, it is seen that the magnetostriction coefficient increases with increasing applied magnetic eld and remains almost constant at higher eld, i.e.…”
Section: Magnetostrictive Properties (L and Dl/dh)mentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35][36][37] More recent studies consider that the IS values correlated with the structural data can be better used for site assignments in cobalt ferrite. Consequently, the sextet with lower IS (~ 0.19 mm s -1 , relative to -iron) is assigned to iron in tetrahedral sites (from inter-nuclear distance arguments) [35] and the sextet with higher IS (0.32 mm s -1 ) corresponds to octahedral iron sites.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%